2011
DOI: 10.2527/jas.2010-3033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increasing choice white grease in corn- and sorghum-based diets on growth performance, carcass characteristics, and fat quality characteristics of finishing pigs1

Abstract: A total of 120 pigs (60 barrows and 60 gilts; TR4 × PIC 1050; 54.4 kg initial BW) were used in an 83-d study to evaluate the effects of added fat in corn- and sorghum-based diets on growth performance, carcass characteristics, and carcass fat quality. Treatments were arranged in a 2 × 3 factorial with grain source (corn or sorghum) and added fat (0, 2.5, or 5% choice white grease; CWG) as factors. There were 2 pigs (1 barrow and 1 gilt) per pen and 10 replicate pens per treatment. Pigs and feeders were weighed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 21 publications
1
20
0
3
Order By: Relevance
“…However, add ed fat did increase backfat depth. Similarly, Apple et al (2009b) and Benz et al (2011b) reported that carcasses from pigs fed added dietary fat, regardless of source, had greater average backfat depths than carcasses from pigs fed a diet without added fat. This would be expected as the pig is consuming a high energy diet and once the pig has reached the break point of protein accretion, they will rapidly fatten (Pettigrew and Esnaola, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, add ed fat did increase backfat depth. Similarly, Apple et al (2009b) and Benz et al (2011b) reported that carcasses from pigs fed added dietary fat, regardless of source, had greater average backfat depths than carcasses from pigs fed a diet without added fat. This would be expected as the pig is consuming a high energy diet and once the pig has reached the break point of protein accretion, they will rapidly fatten (Pettigrew and Esnaola, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Added fat has been shown in some cases to improve HCW and carcass yield (Smith et al, 1999;Jackson et al, 2009) while others have reported no improvements in carcass yield (Engel et al, 2001;Benz et al, 2011). Beaulieu et al (2009) reported that for every 0.10 increase in Mcal/kg of DE, carcass yield improved by 0.20% units.…”
Section: Growth Performance and Carcass Characteristicsmentioning
confidence: 99%
“…Increased carcass backfat depth is the 1 carcass trait most consistently increased with added dietary fat, due to high energy intake (Beaulieu et al, 2009;Benz et al, 2011;Salyer et al, 2012). Because most pork producers are paid on a carcass basis in the U.S., another measurement of response to observe is carcass performance.…”
Section: Growth Performance and Carcass Characteristicsmentioning
confidence: 99%
“…Additionally, weak correlations were found between the various depots' iodine values, suggesting that one depot's iodine value may not be a good predictor of the iodine value of another depot . Backfat generally had a reduced iodine value when compared to jowl adipose tissue (Benz et al, 2011). In research focused on diet differences (linoleic acid inclusion level, fat inclusion level, and fat source), it was recorded that overall gilts have adipose tissue with higher iodine values than adipose tissue from barrows (Averette Gatlin et al, 2002), possibly due to having a lesser percent of 14:0 (myristic acid) and 16:0 (palmitic acid) and greater percent of 18:2 n-6 (linoleic acid) in their adipose tissue (Martin et al, 1972).…”
Section: Lipidmentioning
confidence: 99%